Analisis Tingkat Literasi Keuangan Dalam Pengelolaan Finansial Pribadi Mahasiswa - Muhammad Hafizd Fauzi; Sri Diana Putri; Rahma Agustina Fadhilah; Mirna Kurniati; Annisa Rizki Pebriani; Muhamad Raihan Eka Putra; Rama Wijaya Abdul Rozak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Financial literacy is one of the important skills that must be possessed by individuals, especially students, based on situations that require the ability to manage their personal finances. This research uses a qualitative approach with a focus on semi-structured interviews to gather information. The research participants were 12 students with different ages, genders, universities, study programs and faculties. The results of the analysis from interviews showed that students who live in boarding houses or with their parents can apply financial literacy for financial management, even without realizing it. However, financial literacy is more applied to students who live in boarding houses.